Love and affectionate touch toward romantic partners all over the world - Agnieszka Sorokowska; Marta Kowal; Supreet Saluja; Toivo Aavik; Charlotte Alm; Afifa Anjum; Kelly Asao; Carlota Batres; Aicha Bensafia; Boris Bizumic; Mahmoud Boussena; David M. Buss; et al. (Scientific Reports, 2023)
Abstract Touch is the primary way people communicate intimacy in romantic relationships, and affectionate touch behaviors such as stroking, hugging and kissing are universally observed in partnerships all over the world. Here, we explored the association of love and affectionate touch behaviors in romantic partnerships in two studies comprising 7880 participants. In the first study, we used a cross-cultural survey conducted in 37 countries to test whether love was universally associated with affectionate touch behaviors. In the second study, using a more fine-tuned touch behavior scale, we tested whether the frequency of affectionate touch behaviors was related to love in romantic partnerships. As hypothesized, love was significantly and positively associated with affectionate touch behaviors in both studies and this result was replicated regardless of the inclusion of potentially relevant factors as controls. Altogether, our data strongly suggest that affectionate touch is a relatively stable characteristic of human romantic relationships that is robustly and reliably related to the degree of reported love between partners.